Nuances e interfaces da informalidade na cidade de Palmas: subsídios à compreensão da relação capital/ trabalho no capitalismo contemporâneo - Cerqueira, Eder da Silva (Universidade Federal do Tocantins, 2016)
This research had as its starting point the recognition of parts of the population who have always had to resort to the informal labor market to ensure their survival. In Brazil, the configuration of the labor market differs from that of developed countries, mainly from Europe, where there was formation of a state of full social welfare. Since the mid-1980s with the restructuring of production and intensification (neo) liberal, has seen the (re) set in relation to capital x work, which has had major consequences as a lower supply of formal jobs, and enhance and precarious working conditions. Since then, a growing number of workers who can not find a job in the formal labor market, leaving them the "option" to exercise their activities in the informal labor. The present study aims to understand the genesis of informality in the city of Palmas, the capital of the State of Tocantins. Most of the theories that explain the informality, base their arguments on the argument that this phenomenon results from a reduction of jobs in the industrial sector.However, it is observed that also in regions / cities that do not have a significant participation of the industrial sector in economic activity, there is a large portion of workers working in the informal sector. What are the causes of the manifestation of informality in these localities? What are the main variables that contribute to this phenomenon also manifests itself in these regions? There are factors of moral / cultural / psychological / religious influence in shaping this phenomenon? What are the advantages and disadvantages are attributed to the employment and work in the informal workers who work in the informal market? Anyway, what is the genesis of informality in a location where industrial production was, and is insignificant in terms of its percentage share in economic activity? To try to understand these questions, we analyzed interviews with workers living in the city of Palmas performing their work activities in the informal labor market. The work trajectories analyzed show the complexity of the issue of informal work market. Armed with the data obtained through interviews, we could better understand the heterogeneity and complexity involving the universe of informal labor market in Brazil, having been revealed aspects that are restricted to everyday scenes in these workers. There is undoubtedly a broad sense that the universe involves the informal labor market. But the universe of streets turned out to be a universe that much more complex and diverse than it may seem.